2002
DOI: 10.1148/radiol.2241011262
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma: Meta-Analysis of Randomized Controlled Trials

Abstract: In patients with unresectable HCC, chemoembolization significantly improved the overall 2-year survival compared with nonactive treatment, but the magnitude of the benefit is relatively small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
445
1
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 778 publications
(470 citation statements)
references
References 45 publications
6
445
1
8
Order By: Relevance
“…As expected, we did not identify any RCT comparing lipiodol TACE versus best supportive care performed after 2002 and therefore not already included in the previous meta-analyses. (14,15) Hence, we were unable to update the results already presented concerning the survival benefit of TACE over no intervention. The other RCTs that were identified had different design and treatment arms and were focused on the comparison of different TACE techniques or protocols, (23)(24)(25)30) on the comparison of lipiodol TACE and either intravenous or transarterial chemotherapy (26,27) and on the use of lipiodol TACE alone versus lipiodol TACE combined with amiodarone or bevacizumab.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As expected, we did not identify any RCT comparing lipiodol TACE versus best supportive care performed after 2002 and therefore not already included in the previous meta-analyses. (14,15) Hence, we were unable to update the results already presented concerning the survival benefit of TACE over no intervention. The other RCTs that were identified had different design and treatment arms and were focused on the comparison of different TACE techniques or protocols, (23)(24)(25)30) on the comparison of lipiodol TACE and either intravenous or transarterial chemotherapy (26,27) and on the use of lipiodol TACE alone versus lipiodol TACE combined with amiodarone or bevacizumab.…”
Section: Discussionmentioning
confidence: 97%
“…(31)(32)(33)(34)(35) Use of lipiodol TACE in the treatment of HCC is based on meta-analyses of RCTs comparing embolization or chemoembolization versus conservative management. (14,15) A recent Cochrane meta-analysis (36) whose methodology has been criticized by several experts (37,38) -questioned the evidence supporting the beneficial effect of TACE over no intervention on survival in patients with HCC. The authors of this Cochrane review advocated for more efforts to investigate the benefits of TACE through adequately powered, bias-protected trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, chemoembolisation for HCC is mainly used in advanced stage patients who cannot be treated with transcatheter arterial embolisation (TAE), or whose hepatic function standby capacity is low. Furthermore, Camma et al (2002) have reported that chemoembolisation has a significant therapeutic benefit, compared with more conservative therapies, based on the data from 18 radiotherapy centres. Several attempts have been made to take advantage of the properties of lipiodol, by coinfusion of lipiodol and anticancer agents such as zinostatin stimalamer (SMANCS s ), doxorubicin, epirubicin, mitomycin C and cisplatin Kanematsu et al, 1984;Ohishi et al, 1985;Yamashita et al, 1985;Kobayashi et al, 1986;Fukushima et al, 1988;Shibata et al, 1989).…”
mentioning
confidence: 99%